2022
DOI: 10.1002/asna.20220010
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale asymmetry in galaxy spin directions: Analysis of galaxies with spectra in DES, SDSS, and DESI Legacy Survey

Abstract: Multiple previous studies using several different probes have shown considerable evidence for the existence of cosmological‐scale anisotropy and a Hubble‐scale axis. One of the probes that show such evidence is the distribution of the directions toward which galaxies spin. The advantage of the analysis of the distribution of galaxy spin directions compared to the cosmic microwave background anisotropy is that the ratio of galaxy spin directions is a relative measurement, and therefore less sensitive to backgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 182 publications
6
19
0
Order By: Relevance
“…Therefore, limiting the redshift to 0.1 is expected to show low statistical significance. The low statistical significance shown in (Iye et al, 2021) agrees with the random distribution in that redshift range as shown in (Shamir, 2020c(Shamir, , 2022c.…”
Section: Iye Et Al (2021) Performed Experiments With Two Datasetssupporting
confidence: 78%
See 3 more Smart Citations
“…Therefore, limiting the redshift to 0.1 is expected to show low statistical significance. The low statistical significance shown in (Iye et al, 2021) agrees with the random distribution in that redshift range as shown in (Shamir, 2020c(Shamir, , 2022c.…”
Section: Iye Et Al (2021) Performed Experiments With Two Datasetssupporting
confidence: 78%
“…Also, an experiment reported in (Shamir, 2020c) used galaxies limited to z < 0.15, and showed that the statistical significance of the dipole axis was below 2σ. A similar experiment (Shamir, 2022c) also showed that the dipole axis is not statistically significant in the lower redshift ranges, including 0 < z < 0.1. Therefore, limiting the redshift to 0.1 is expected to show low statistical significance.…”
Section: Iye Et Al (2021) Performed Experiments With Two Datasetsmentioning
confidence: 80%
See 2 more Smart Citations
“…The ability to annotate galaxies automatically allowed analyses based on far larger catalogs that are not subjected to the bias of the human perception. Such analysis showed clear statistical signal of non-random distribution and dipole axis alignment in data taken from SDSS [501], Pan-STARRS [502], Hubble Space Telescope [503], DES [504], and DESI Legacy Survey [505]; all data sets show very similar profiles of asymmetry, and dipole axes well-within 1 σ statistical error from each other [506]. The axes were observed in data collected from telescopes located in the Northern hemisphere [502], and nearly identical patterns were observed when using data collected by telescopes in the Southern [505] hemispheres.…”
Section: Dipole In the Distribution Of Galaxy Spin Directionsmentioning
confidence: 88%